2020
DOI: 10.1126/scitranslmed.aay9013
|View full text |Cite
|
Sign up to set email alerts
|

cGAS-STING–mediated DNA sensing maintains CD8 + T cell stemness and promotes antitumor T cell therapy

Abstract: Although cGAS-STING–mediated DNA sensing in tumor cells or phagocytes is central for launching antitumor immunity, the role of intrinsic cGAS-STING activation in T cells remains unknown. Here, we observed that peripheral blood CD8+ T cells from patients with cancer showed remarkably compromised expression of the cGAS-STING cascade. We demonstrated that the cGAS-STING cascade in adoptively transferred CD8+ T cells was essential for antitumor immune responses in the context of T cell therapy in mice. Mechanistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(116 citation statements)
references
References 59 publications
8
101
0
Order By: Relevance
“…A compromised expression of the cGAS-STING cascade has also been confirmed in CD8+T cells from cancer patients, with reduced stem-like central memory CD8+T cells subsets ( 35 ). This is a selective advantage for survival and growth for cancers ( 36 ).…”
Section: Introductionmentioning
confidence: 90%
“…A compromised expression of the cGAS-STING cascade has also been confirmed in CD8+T cells from cancer patients, with reduced stem-like central memory CD8+T cells subsets ( 35 ). This is a selective advantage for survival and growth for cancers ( 36 ).…”
Section: Introductionmentioning
confidence: 90%
“…Finally, tumor cell-derived cGAMP can also be transferred to host DCs by the folate transporter SLC19A1 and then directly binds to STING, activating it in DCs [ 84 ]. A recent study more directly demonstrated that cell-autonomous STING promoted the maintenance of stem cell-like CD8 + T cells and augmented antitumor T cell responses, and mechanistically, cGAS-STING-mediated type I interferon signaling reinforced the stem cell–like CD8 + T cell differentiation program mainly by restraining Akt activity [ 85 ].…”
Section: The Antitumor Functions Of the Cgas-sting Signaling Pathwaymentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint this version posted March 8, 2021. ; https://doi.org/10.1101/2021.03.08.434225 doi: bioRxiv preprint 14 thereby increases innate and adaptive immune signaling in tumors (33). The cGAS-STING pathway is emerging as a key regulator of cancer development and therapeutic response with roles in tumor development, metastasis, immunomodulation, senescence, viral defense, and autophagy (34)(35)(36)(37)(38)(39)(40).…”
mentioning
confidence: 99%